Synthesis and structural characterization of two diiron complexes with diphenyl-2-pyridylphosphine or tris(3-fluorophenyl)phosphine. (2nd November 2018) - Yan, Lin; Liu, Xu-Feng; Jiang, Zhong-Qing; Wu, Hong-Ke
Abstract: In this paper, two diiron complexes have been prepared by CO exchange and structurally characterized. Treatment of complex [Fe2 (CO)6 { μ -SCH2 CH(CH2 O2 CCH3 )S}] (1 ) with diphenyl-2-pyridylphosphine in the presence of Me3 NO·2H2 O as the decarbonylating agent gave the corresponding monophosphine-substituted complex [Fe2 (CO)5 {Ph2 P(2-C5 H4 N)}{ μ -SCH2 CH(CH2 O2 CCH3 )S}] (2 ) in 85% yield. Similarly, complex [Fe2 (CO)5 {P(3-C6 H4 F)3 }{ μ -SCH2 CH(CH2 O2 CPh)S}] (4 ) was obtained in 78% yield by the reaction of complex [Fe2 (CO)6 { μ -SCH2 CH(CH2 O2 CPh)S}] (3 ) with tris(3-fluorophenyl)phosphine. The new complexes2 and4 have been characterized by elemental analysis, IR spectroscopy, NMR spectroscopy, as well as by X-ray diffraction analysis.